Wykorzystanie publikacji francuskich przy realizacji nagrobków na cmentarzach Warszawy w latach 1840-1860. Wzornik Josepha Marty'ego - Wiraszka, Marta (Saeculum Christianum. Pismo Historyczne, 2019)
The article in question is a continuity of the subject brought up in the magazine ”Artifex Novus” published in October 2017. Its first part referred to the tombstones created on the ground of works printed in Paris in 1832 on the pages of two illustrated magazines whose authors were Ferdinando Quaglia and Louis-Marie Normand respectively. The other part was dedicated to the pattern book by Joseph Mart and the objects performed on its ground. Collected pieces of information enable us to conclude that between 1840 and 1860 on the premises of the necropoleis of Warsaw a minimum of 20 tombstones, with the forms following those published in the above mentioned magazines, were raised. The vast majority of preserved examples, as many as 14, can be found on the premises of the Powązki Cemetery, another three were discovered at the Evangelical Augsburg Cemetery and two at the Evangelical Reformed Cemetery. Moreover, it has been stated that such tombstones happen to be funded on the premises of necropolies located outside the boundaries of the capital e.g. in Lublin, Pułtusk, Radom etc. Even though none of the tombstones was signed, it can be concluded the center of production and distribution was Warsaw and the stonework manufactures in operation in the city. Among others, attention was drawn to two manufactures: the one of Jan Ścisłowski (1805-1847) located at 6 Powązkowska Street, inherited and led by his two sons-in-law: Antoni Messing (1821-1867) and Jan Bernard Sikorski (1832-1906), and the other belonging to the Mantzl family, Jan Józef senior – the father (1806-1875) and Józef Jan junior, – the son (1834-1906), the manufacture previously located at 19 Chłodna Street. The tombstones funded and co-funded by relatives and friends were copings to graves of the wealthy, high officials, militaries, real estate and factory owners, entrepreneurs, merchants as well as craftsmen. The offer of the stonework manufactures in Warsaw reflected the taste of the elite, in the vast majority of Catholics of aristocratic descendance willing to show pro-French likeness and respect to the culture in question, having it as more sophisticated than the one dating back to the monarchy of Louis the XIV, and in particular, forming bonds with the empire of Napoleon Bonaparte the I.